Perspectives on a Cybersecurity Governance Framework Integrating Blockchain, Artificial Intelligence, and Legal Base for one Organization - Toapanta T, Moisés; Buenaño, Jeanette Jordán; Vayas C, Santiago; Nogales, P, Rubén; Del Pozo D, Rodrigo; Orizaga T, Antonio; Andrade A, Diego (Journal of Posthumanism, 2025)
Cybersecurity governance issues remain persistent worldwide. One of the key causes is the lack of appropriate models, prototypes, or guidelines that effectively incorporate emerging technologies such as blockchain and artificial intelligence, while being grounded in national legal frameworks or aligned with international standards. The objective of this research is to analyze and define a prototype for the integration of a "Framework for Cybersecurity Governance Based on Blockchain, Artificial Intelligence, and Legal Foundations for Organizations." A deductive method and exploratory research approach were employed to analyze scholarly articles, standards, laws, regulations, and official websites related to the topic. The study resulted in the identification of relevant actors for the development of a cybersecurity governance framework, an algorithm for its analysis, and a prototype framework. The findings suggest that all organizations, based on simulations involving the identified actors, should aim for a performance level above 75%. Organizations scoring 75% or lower must seek strategies to reach a higher range—between 76% and 95%—to effectively mitigate risks, threats, and vulnerabilities in cybersecurity governance management.